2016
DOI: 10.1179/2042618614y.0000000082
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability of a modified version of Delitto et al.’s classification-based system for low back pain: a pilot study

Abstract: Study design: Observational inter-rater reliability study. Objectives: To examine: (1) the inter-rater reliability of a modified version of Delitto et al.'s classificationbased algorithm for patients with low back pain; (2) the influence of different levels of familiarity with the system; and (3) the inter-rater reliability of algorithm decisions in patients who clearly fit into a subgroup (clear classifications) and those who do not (unclear classifications). Methods: Patients were examined twice on the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…Measuring reliability and agreement between raters for the TBC assessment is crucial in order to compare measurements between therapists, observe classification patterns and consistency, and also explore disagreements among them, contributing to the classification methods' further enhancement. This study presented a substantial agreement (k = 0.62) between raters, conflicting with previous studies by Apledoorn et al (2016) [41], Fritz et al…”
Section: Discussioncontrasting
confidence: 99%
“…Measuring reliability and agreement between raters for the TBC assessment is crucial in order to compare measurements between therapists, observe classification patterns and consistency, and also explore disagreements among them, contributing to the classification methods' further enhancement. This study presented a substantial agreement (k = 0.62) between raters, conflicting with previous studies by Apledoorn et al (2016) [41], Fritz et al…”
Section: Discussioncontrasting
confidence: 99%
“…If we consider the PAM analysis as a valid classification method, this relatively low agreement revealed the weakness of the 2007 TBC system. A moderate [23][24][25][26] and moderate to good [21,29,38,39] inter-observer reliability have been reported for the TBC system. To the authors' knowledge, this is the first study that examine the TBC classification using clustering by PAM analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Stanton et al showed that the TBC criteria do not guarantee that patients comply with a single intervention, but that 25% of patients can meet criteria for more than one subgroup [ 23 ]. In addition, the prevalence of patients with “unclear classification” in early versions of TBC system has been estimated between 26 and 50 percent [ 23 , 24 , 38 , 40 ]. The developers of the 2007 TBC system also stated that this system had its limitations and needed to refine the algorithm [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations